2022
DOI: 10.3389/fnagi.2021.718648
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical Activity in Older Adults Is More Influenced by Cognitive Task Complexity Than Concurrent Walking

Abstract: Human cognitive-motor performance largely depends on how brain resources are allocated during simultaneous tasks. Nonetheless, little is known regarding the age-related changes in electrocortical activity when dual-task during walking presents higher complexity levels. Thus, the aim of this study was to investigate whether there are distinct changes in walking performance and electrocortical activation between young and older adults performing simple and complex upper limb response time tasks. Physically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Another factor involved in the interaction between gait and cognitive tasks is task complexity, but only a few studies have investigated its influence on cognitive DTC, with variable results. Some studies have reported higher cognitive DTC as cognitive task complexity increases (34)(35)(36). The effect seems to be influenced by age and cognitive domains involved (35-39).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another factor involved in the interaction between gait and cognitive tasks is task complexity, but only a few studies have investigated its influence on cognitive DTC, with variable results. Some studies have reported higher cognitive DTC as cognitive task complexity increases (34)(35)(36). The effect seems to be influenced by age and cognitive domains involved (35-39).…”
Section: Introductionmentioning
confidence: 95%
“…Our results on SRT are in line with previous studies showing a deterioration in reaction time when performing another task simultaneously, such as contralateral movements (65), a secondary cognitive task (66), a postural task (67) or walking (68, 69). However, previous studies have reported that cognitive DTC is highly variable depending on several factors such as attention (70), age and gender (18,35,36,38,(71)(72)(73)(74), task type and difficulty (35,36,39,63,70,75), and these variables show a complex interaction. In addition, several studies have shown that cognitive performance in DT did not change compared to ST (17,[19][20][21] or even improved (17,18,20,29).…”
Section: E Ect Of Complexity Of the Cognitive Tasksmentioning
confidence: 99%
“…The performance of human cognitive and motor functions largely depends on the allocation of brain resources in synchronous tasks (Vila-Cha et al, 2021). Under increasing task demands, maintaining adequate motor ability depends on the regulation and coordination of cognitive resources.…”
Section: The Relationship Between Allocation Of Cognitive Resources A...mentioning
confidence: 99%
“…Additionally, the N1 component, which is closely related to the initial processing of a stimulus, can represent the demands of early perceptual processing (Hickey et al, 2020;Chen et al, 2022a,b). Finally, the P2 and P3 components of the ERP, representing the response to visual stimuli over the parietal region, are the most common indices for evaluation of cognitive resources (Yang et al, 2020;Reiser et al, 2021;Vila-Cha et al, 2021). The higher the amplitude of these components, the higher the consumption of cognitive resources is generally considered to be.…”
Section: Introductionmentioning
confidence: 99%